Race, culture and schooling : - Murrell, Peter C. (Lawrence Erlbaum Associates, 2007)
Responding to a need for greater cultural competence in the preparation and development of teachers in diverse public school settings, this book investigates the critical developmental and social processes mediating students’ academic identities in those settings posing the greatest challenges to their school achievement and personal development. It provides an accessible, practice-oriented culturally responsive framework for teachers in American schools.